2004
DOI: 10.1111/j.1524-4725.2004.30008.x
|View full text |Cite
|
Sign up to set email alerts
|

Microfoam Ultrasound-Guided Sclerotherapy of Varicose Veins in 100 Legs

Abstract: Ultrasound-guided foam sclerotherapy is effective in treating varicose veins with high patient satisfaction with results and improvement in quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
1
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 7 publications
3
52
1
2
Order By: Relevance
“…These results are comparable to those achieved with surgical or other interventional endovascular procedures. 7,[10][11][12][13][14][15][16][17][18][19] Our study consisted of a representative number of patients with uncomplicated VVs (59%) and severe venous insufficiency (41%) referred to a vascular outpatient clinic. We have demonstrated that the rate of complete and partial obliteration does not differ between these patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results are comparable to those achieved with surgical or other interventional endovascular procedures. 7,[10][11][12][13][14][15][16][17][18][19] Our study consisted of a representative number of patients with uncomplicated VVs (59%) and severe venous insufficiency (41%) referred to a vascular outpatient clinic. We have demonstrated that the rate of complete and partial obliteration does not differ between these patients.…”
Section: Discussionmentioning
confidence: 99%
“…7,[10][11][12][13][14][15][16][17] In the only published US study, Bergan et al demonstrated the efficacy of EFS for the management of CVI in 332 patients (261 uncomplicated VVs, 56 severe CVI, six venous angiomata, and nine KT syndrome), with satisfactory obliteration in all treated veins (average of 2.89 treatments/limb) and a 99% ulcer healing rate at the 6-week follow-up. 7 O'Hare et al achieved 93% obliteration in 165 patients (185 truncal veins) at 2 weeks and 74% complete and 10% partial obliteration at 6 months post-treatment with EFS.…”
Section: Adverse Eventsmentioning
confidence: 99%
See 2 more Smart Citations
“…Immediate or early closure in medium-to-large veins was achieved in over 85% cases usually requiring more than one sitting; [31][32][33] 80-90% of these remained occluded 3 years after foam sclerotherapy. 34 High patient satisfaction and significant improvement in symptoms and QoL was noted at a mean follow-up of 2 years after foam sclerotherapy.…”
Section: Sclerotherapy (Liquid and Foam)mentioning
confidence: 99%